PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA ASN DENGAN DIMEDIASI KESIAPAN UNTUK BERUBAH PADA UPT PUSKESMAS JANGKAR - Aprilia, Ila Aulia; Pramitasari, Triska Dewi; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2024)
This study aims to determine the impact of transformational leadership, work environment, and motivation on ASN performance by mediating readiness to change on UPT Puskesmas Jangkar. The population in this study is ASN on UPT Puskesmas Jangkar, which is a simple probability sampling method that does not consider the population in this study. The sampling uses saturated samplings, which are sample determination techniques when all members of the population are sampled. Data analysis and hypothesis testing in research using Structural-partial equation model Least square (PLS-SEM). The results of the hypothesis are tested directly using the PLS 3.0 smart application. Demonstrate that transformational leadership has a positive but non- significant influence on the willingness to change, and the working environment has a significant positive impact on the readiness to change. Transformational leadership has a significant positive impact on performance, the working environment has a positive but non-significant impact on Performance, and the motivation for work has a negative but not significant effect on performance. Preparedness to change has a positive but insignificant impact on performance. Transformational leadership has a positive but non-significant impact on Performance through Preparedness for Change, a working environment with a positive yet insignificant influence on Performance via Preparation to Change, and work motivation with a positive but not significant impact on Output through Preparation for Change.